Pemberdayaan masyarakat melalui pengolahan sampah anorganik menjadi barang dekoratif bernilai ekonomis - Huriatul Masdar; Muhammad Yulis Hamidy; Fifia Chandra; RM Riadi; Yulia Irvani Dewi; Nurfi Pratiwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Garbage is the leftover product from every human daily activity that is thrown away which, if not managed properly, can cause environmental and health problems. Waste bank is a form community participation in waste management. Air Putih Sub-dsitrict already has a waste bank that is actively operating. However its activities are still limited to collect inorganic waste from customers and sell it to collectors. In order to increase the value of inorganic waste collected in the waste bank, a training to decorate used items using decoupage technique was conducted. Waste bank managers and Empowerment Family Welfare (PKK) members were participated in this training. In addition, a training how to use social media as a marketing media were performed. The results showed that the target community's skills had been achieved in processing inorganic waste into decorative items with higher economic value. Meanwhile, the sustainability of production and the economic impact resulting from these trainings still require further evaluation.